The Important Role of English Songs in Learning English For Young Learners - Fitriana, Rizkia Odie (Pustaka Digital Indonesia, 2021)
The atmosphere of the class will come alive if the teacher gives life to his class, for example giving encouragement and motivation every day. Teachers must understand how to create effective classes to begin the learning process. The media of the song can be used for learning activities in the classroom. Songs are used to add new vocabulary in English, facilitate the ability to speak, and practice hearing ability. The method used is qualitative with a descriptive approach. The result of this study is to improve the understanding of teachers and young people on the importance of learning from an English song to improve the ability of the English language